Darkness, take my hand - Lehane, Dennis (William Morrow, 2013)
Boston private detectives Patrick Kenzie and Angela Gennaro try to protect the son of a prominent psychiatrist in the midst of an ever-growing body count and a list of clues that point impossibly to a serial killer who has been in prison for twenty years.